Race biology - Saura, Anssi (Hereditas, 2020)
BACKGROUND: The founders of Hereditas envisioned that race biology would be a major subject that had social applications with utmost importance in the near future. Anthropometrics was in this context understood to be the pure and eugenics the applied science. Sweden had a long tradition in physical anthropometry. Herman Lundborg, member of the advisory board of Hereditas, united the anthropometric and eugenic approaches in a synthesis. He was the first head of the Institute for Race Biology in Sweden. The contents of Hereditas reflect the development of race biology in the Nordic countries. CONCLUSIONS: The initial enthusiasm for applied race biology did not last long. In the 1920’s Hereditas carried papers on both physical anthropology and eugenics. Most paper dealt, however, with human genetics without eugenic content. Two papers, published in 1921 and 1939 show how the intellectual climate had changed from positive to negative. Finally only human genetics prevailed as the legitimate study of the human race or humankind. A belated defense of eugenics published in 1951 did not help; geneticists had abandoned anthropometrics for good around the year 1940 and eugenics about a decade later. In spite of that, eugenic legislation was amended astonishingly late, in the 1970’s. The development was essentially similar in all Nordic countries.